Analysis of Effect on the Working Environment, Work Motivation, and Discipline on Performance Employees of PT. Seimitsu Indonesia - Daspar; Liska Restiani (Manajemen Bisnis, 2022)
ABSTRACT This study aims to examine the influence of the work environment, work motivation, and work discipline on the performance of employees of PT Fuji Seimitsu Indonesia. The sampling method used was technique sampling non probability saturated sampling technique so that the entire population that is, 70 people were sampled. This type of research is quantitative, for data This research was obtained from a questionnaire that has been filled in by the employees of PT Fuji Seimitsu Indonesia. The analytical method used is the validity test, reliability test, classical assumption test, multiple linear analysis test, and coefficient determination in the IBM SPSS 22 for Windows program. The results of the work environment hypothesis test show t arithmetic> t table (2.016> 1.997) then there is an influence between the work environment on performance employees, the results of the work motivation hypothesis test show t arithmetic <t table (-0.823 <1.997) then there is no influence between work motivation on employee performance, while the results of the work discipline hypothesis test showed t count> t table (5.107> 1.997) then there is an influence between work discipline on employee performance, and simultaneously shows Fcount> F table (22,582> 2,744) then there is an influence between work environment, work motivation, and work discipline on employee performance.